Chitosan nanocomposite fibers supported copper nanoparticles based perceptive sensor and active catalyst for nitrophenol in real water. (1st March 2019) - Khan, Sher Bahadar; Ali, Fayaz; Akhtar, Kalsoom
Graphical abstract: Highlights: CH + GO nanocomposite fibres were prepared and Cu nanoparticles were grown on them. Cu@CH + GO nanocomposite was applied for the electrochemical detection of 4-NP. Cu@CH + GO nanocomposite exhibited high sensitivity toward the detection of 4-NP. Cu@CH + GO nanocomposite is economical and a highly efficient catalyst for 4-NP. Cu@CH + GO catalyst showed stability and reusability for 4-NP detection and reduction. Abstract: In this report, copper nanoparticles templated at chitosan-coated graphene oxide (GO) nanocomposite fibers (Cu@CH + GO) were prepared via solution-based fiber formation followed by treatment with a metal salt solution and NaBH4 and utilized for the detection and catalytic reduction of 4-nitrophenol (4-NP). Cu@CH + GO exhibited a high sensitivity of 1.729 ± 0.027 μAmM –1  cm –2 and a detection limit of 3.5 mM toward 4-NP. In addition, high catalytic activity was observed for the reduction of 4-NP with an apparent rate constant of 1.310 ± 0.093 min –1 using 7 mg of Cu@CH + GO catalyst. Besides the good catalytic activities of Cu@CH + GO, it could be easily recovered by simply pulling the fiber from the reaction medium. Moreover, Cu@CH + GO catalyst was also examined in real samples and found to be efficient in the detection and reduction of 4-NP. This novel approach provides a new route for simultaneous detection and reduction of 4-NP and can be a time and cost-effective tool for environmental safety.